Learning Feedforward Control Of MIMO Nonlinear Systems Using U-Model - Azhar, ASS (2020)
In this paper, a learning feedforward controller (LFFC) using the U-model is proposed for a better tracking control of multivariable nonlinear systems over a finite time interval. The multivariable system is modelled using the U-model and the LFFC is established using Newton-Raphson method. U-model significantly simplifies the online synthesis of the feedforward control law. The proposed technique is verified on 2-link robot manipulator in real-time. The performance of the proposed U-model based LFFC is compared with a number of schemes under varying load conditions.